Pain, Disability, and Art: A Response to Verpaelst - Stahl, Devan (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
Pain is inherently subjective and culturally mitigated and so it is difficult to measure and mitigate. Art creation has the ability to be therapeutic to persons in chronic pain.